CD117 and Ki-67 expression in gastrointestinal stromal tumors of various morphological variants and localization - Shpon’ka I.S. (Морфологія, 2014)
Background. Gastrointestinal stromal tumors are considered as the most frequently occurring tumors of mesenchymal origin in the gastrointestinal tract. Despite active research work in this field many problems in the diagnosis and prognosis of the disease are still unresolved. Objective. To evaluate the interrelations between clinical and morphological characteristics of gastrointestinal stromal tumors, including expression of proliferative activity marker Ki -67, and specific histogenetic marker CD117. Methods. 47 samples were divided into 2 groups: СD117-positive and СD117–negative; each group was divided into subgroups using the following criteria: age, histological structure, localization, expression of Ki-67. Statistical processing of the data included nonparametric tests. Results. Gastrointestinal stromal tumors are more frequent in patients of age group over 60 years, with localization in the stomach and fusiform type of the structure. Comparative analysis of the subgroups with different expression of СD117 did not reveal any significant differences. Conclusion. Data analysis did not reveal any interrelation between the expression of CD117 and clinical or morphological parameters (p>0,05). However, the high rate of Ki-67 expression in stomach neoplasms is less common than in tumors of other localization. Taken together these data evidence the existence of the interrelations between immunohistochemical characteristics and clinical data.